Depositional environment variations and organic matter accumulation of the first member of the Qingshankou formation in the southern Songliao Basin, China - Ma, Yan; Jinlai, Feng (Frontiers in Earth Science, 2023)
Abstract：The organic-rich shale in the first member of the Qingshankou Formation which located in the southern Songliao Basin is regarded as a high quality source rock in East China. Geochemistry parameters were utilized to illustrate the formation and preservation conditions of Qing 1 member in Changling sag, southern Songliao basin.In current study, from longitudinal continuity, the samples of the organic geochemistry and elemental geochemistry were collected and systematically analyzed. This aims at determining the paleosalinity, paleoclimate, paleoredox conditions, paleoproductivity and to reconstruct its depositional paleoenvironment. According to total organic carbon (TOC) content, the Qing 1 member in Changling sag can be classified into two intervals, which are the lower part and the upper part, with high TOC content and low TOC content, respectively. It can be proved from the results of geochemical indicators that, under warm and humid climatic conditions the relatively lower part was generated in the anoxic environment. Terrigenous input brought nutrients to the water body of the lake, made algae flourish, and had a relatively high paleoproductivity of the lake, which imposed a vigorous impact on the accumulation of organic matter. The upper part is mainly deposited under weekly oxidizing conditions, with gradually enhanced oxidation and reduced productivity. In contrast to the lower shale, the terrigenous inflow is relatively low. TOC content in the Qing 1 member has a positive relavance with the paleoredox conditions, as well as the paleosalinity conditions, indicating that good preservation are favorable for the organic matter accumulating. A depositional model is proposed for organic matter accumulation of this shale.The upper part was in a relatively hot and dry paleoclimate, with a low degree of organic matter enrichment.While the lower part had a warm and humid paleoclimate, with the input of terrestrial organic matter into the primary productivity of the lake basin, with a high degree of organic matter enrichment.